Fish Health Management Considerations in Recirculating Aquaculture Systems – Part 2: Pathogens - Roy Yanong (EDIS)
Recirculating aquaculture systems, also known as water reuse systems, have become more and more popular. Recirculating systems are commonly found in aquaculture facilities, wholesale and retail tropical fish facilities, and public aquaria. However, in order to successfully and most efficiently operate one of these systems, a good understanding of fish health management considerations is critical. This circular is Part 2 in a three-part series dealing with management of fish health in recirculating systems. It explains the role of pathogens (potential disease-causing organisms) in these systems. Published December 2003.